2014
DOI: 10.4236/jamp.2014.26051
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Influence of Grain Size and Loading Conditions on the Deformation of a Polycrystalline Aluminum Alloy

Abstract: This work is concerned with numerical simulations of surface roughening in a polycrystalline aluminum alloy. Using 3D finite difference model, high-resolution simulations are conducted. Effects of loading conditions and grain size on surface roughening and mesoscale deformation processes in AL6061-T3 aluminum alloy under quasistatic uniaxial tension are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…It should be noticed that depending on the mechanical impact on the material the structure of surface damages will be varied. This numerously experimentally proved evidence testifies for the fact that surface layer of the material is the most "sensitive" in order to be used for characterization the kinetics of damage accumulation at various loading modes [8,9]. These above mentioned properties of material self-organization are widely used at development of instrumental techniques for fatigue fracture diagnostics of aircraft structures [10][11][12].…”
Section: Introductionmentioning
confidence: 83%
“…It should be noticed that depending on the mechanical impact on the material the structure of surface damages will be varied. This numerously experimentally proved evidence testifies for the fact that surface layer of the material is the most "sensitive" in order to be used for characterization the kinetics of damage accumulation at various loading modes [8,9]. These above mentioned properties of material self-organization are widely used at development of instrumental techniques for fatigue fracture diagnostics of aircraft structures [10][11][12].…”
Section: Introductionmentioning
confidence: 83%
“…To build a three-dimensional model of the grain structure, the solid bodies are constructed through the extrusion of two-dimensional microsection with a depth of 10 µ m, which corresponds to the average grain size in the normal direction of the sheet metal. For appropriate numerical accuracy, a Finite Element model with minimal three layers is used, which is also proposed by Zinovieva et al [27]. Panin et al identified that the first layer which is closest positioned to the surface has the main influence on the surface roughening [28].…”
Section: Numerical Prediction Of Strain-induced Roughening 21 the App...mentioning
confidence: 99%
“…Экспериментальные результаты и данные математических моделей свиде-тельствуют о том, что складкообразование, гофриро-вание, шахматное распределение областей экструзии и интрузии и т. д. являются характерными процессами при формировании деформационного рельефа и возникают при различных условиях нагружения в поли-и мо-нокристаллах [1][2][3][4][5][6][7][8][9][10]. Складкообразование реализуется при разных способах деформации, имеет многообразные проявления и может быть инициировано как скольжени-ем, так и двойникованием.…”
Section: Introductionunclassified
“…В настоящее время накоплен материал по математи-ческому моделированию процессов формирования ше-роховатости поверхности в различных условиях нагру-жения [1,2]. В работе [1] методом конечных элементов было проведено моделирование процесса возникновения шероховатости при пластической деформации образцов поликристаллического алюминия.…”
Section: Introductionunclassified
See 1 more Smart Citation